2018
DOI: 10.1136/neurintsurg-2018-013915
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy 6-24 hours after stroke in trial ineligible patients

Abstract: Approximately 70% (n=142) of the 204 patients presenting 6-24 hours after last known well with NIH Stroke Scale score ≥6 and harboring an ACLVO are DAWN and/or DEFUSE-3 ineligible, most commonly due to large infarct burden (38%). 26% (n=37) of trial ineligible patients with large vessel occlusion strokes received off-label ET and 30% of them achieved functional independence (modified Rankin Scale 0-2) at 90 days. Rates of symptomatic intracranial hemorrhage and mortality were 8% and 24%, respectively CONCLUSIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 18 publications
4
70
0
3
Order By: Relevance
“…However, as discussed earlier, both trials, because of restrictive radiographic selection criteria, limit their generalizability to many patients with ELVO. For example, a single-center study of patients presenting 6–24 hours after last known well showed that 70% of these patients with anterior circulation ELVO were DAWN and/or DEFUSE 3 ineligible 22. Yet, thrombectomy in these patients resulted in rates of good clinical outcomes comparable to those of DAWN and DEFUSE 3 eligible patients 22…”
Section: Indications For Thrombectomymentioning
confidence: 99%
“…However, as discussed earlier, both trials, because of restrictive radiographic selection criteria, limit their generalizability to many patients with ELVO. For example, a single-center study of patients presenting 6–24 hours after last known well showed that 70% of these patients with anterior circulation ELVO were DAWN and/or DEFUSE 3 ineligible 22. Yet, thrombectomy in these patients resulted in rates of good clinical outcomes comparable to those of DAWN and DEFUSE 3 eligible patients 22…”
Section: Indications For Thrombectomymentioning
confidence: 99%
“…Given these studies, thrombectomy has been included in the 2018 AHA/ASA Stroke Guidelines, recommending thrombectomy for appropriately selected patients 16. Recent studies have also shown that thrombectomy produces good clinical outcomes even in patients with ELVOs who do not meet top-tier evidence criteria in published guidelines 17 18. Of the recent clinical trials and meta-analytical investigations, it is clear endovascular thrombectomy has a significant impact on functional and neurological outcomes for patients with ELVO.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this, multiphase CT angiography data from the ESCAPE (Endovascular treatment for Small Core and Anterior circulation Proximal occlusion with Emphasis on minimizing CT to recanalization times) trial identified a strong association between pre-treatment cerebral pial collaterals and favorable outcome after recanalization [30][31][32] . Similarly, patients with "slow-growing infarcts" due to good collateral circulation in the (DWI or CTP Assessment with Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention with Trevo) and DEFUSE3 (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3) trials benefitted from late thrombectomy (6 to 24 h after stroke onset), likely due to sufficient collateral circulation to maintain tissue viability prior to recanalization up to 24 h post stroke [33][34][35][36][37][38][39][40][41][42] . Rates of hemorrhagic transformation after recanalization are also reduced in patients with good collateral blood flow 4,43,44 .…”
mentioning
confidence: 99%